Quante Italie? Il ritorno al tradizionale cleavage tra Nord e Sud del paese - Bordandini, Paola; Cartocci, Roberto (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
The paper deals with one of the main traits of Italian political culture: distrust and low levels of civicness, as defined and measured by Robert Putnam. Assuming political culture as an independent variable, we aim to draw an updated map of social capital in Italy at regional level using two different measures. The first is an index builds on hard data (2008-2013) concerning rates of blood donors, electoral participation, volunteering, newspaper readerships. The second measure is the general trust’s variable collected by an unusual large sample. Both measures consistently show the old cleavage between Northern and Southern regions to be still very deep. In the seventies and eighties of the past century, political scientists and sociologists were questioning whether there were three, four or five Italies. Our updated indicators, based on hard and self-reported data, suggest that Northern and Central regions show higher levels of social capital than Southern ones. We conclude underlining that the regional civic gap is larger than the Gdp gap.